PENERAPAN SUSTAINABILITY ACCONTING PADA PENGELOLAAN LIMBAH PRODUKSI KERIPIK UBI AJI WIRNA DI KOTA PALOPO - Tadjuddin; Suci; Jumarni; Alya rohalina; Risma; Abrillah; Nur Fadiah; Nayunda Syifa Pamalleri; Diva Kanaya Thabita (Jurnal Edukasi Pengabdian Masyarakat, 2026)
UMKM Aji Wirna, a micro-enterprise producing cassava chips located in Kelurahan Penggoli, Kota Palopo, generates significant solid and liquid production waste—including cassava peels and washing water—that has not been managed optimally, posing risks of environmental pollution. Additionally, the enterprise has not adopted sustainability accounting, leaving environmental costs unidentified and undocumented in its financial records. This community service activity aims to: (1) identify the waste management conditions of UMKM Aji Wirna; (2) provide mentoring on the application of sustainability accounting integrating environmental costs into the financial recording system; and (3) promote the 3R principles (Reduce, Reuse, Recycle) in production waste management. The method used was Participatory Action Research (PAR) comprising four stages: preparation and coordination, socialization and education, implementation mentoring, and evaluation and reporting. The outcomes include a simplified sustainability accounting guide module, a waste management SOP, an integrated environmental cost recording system, and a scientific article published in an accredited national journal. The results show improved understanding of sustainability accounting among UMKM owners, an initial waste segregation system, and cassava peel composting practices that reduce negative environmental impacts while providing added economic value.